Prevalence & Pattern of Opioid Analgesic’s Prescription among Doctors of a Tertiary Care Hospital: Are We Moving Towards an Opioid Epidemic? (Medical Forum Monthly, 2024)
Objective: To identify its possibility in order to warn all concerned to prevent such epidemic. Opioid epidemic has already occurred in many countries including United States of America due to similar reasons in recent years where state of emergency has been declared in October 26, 2017 to achieve opioid stewardship.Study Design: Observational study.Place and Duration of Study: This study was conducted at the Sheikh Khalifa Bin ZayadAlnayan Hospital (CMH) Rawalakot from October 2018 to March 2019.Materials and Methods: Prevalence and pattern of opioid analgesic use was assessed in 72 practicing doctors (42 consultants and 30 general physicians) working in a tertiary care SKBZ hospital (CMH) Rawalakot through a performa.Results: Almost all doctors (98.61%) stated that they prescribe opioids. Only one pediatrician stated that he did not use opioid analgesics. Most of doctors (87.50%) prescribed both injections and oral tablets. However some doctors particularly Anesthetists prescribed only injections (2.77%, nelbuphine & morphine) while few general physicians (9.72%) prescribed only oral tablets of opioid analgesics. Majority (41; 56.94%) of doctors did not counsel their patients about options, risk factors and side effects of opioid analgesics.Conclusion: Opioid analgesics were prescribed by almost all doctors often without following proper guidelines and counseling. This trend can result in impending opioid epidemic of overuse, misuse & addiction. There is a need of physician’s awareness & implementation of updated guidelines to promote reduction and judicious prescription of opioid analgesics.